Credit Card Fraud Detection Using an Efficient Enhanced K- Mean Clustering Algorithm (International Journal of Engineering and Computer Science, 2015)
The purpose of this paper is to study the Different types of frauds in credit card industry and the, effect of creditcard frauds on card holders, merchants, issuers.As credit card becomes the most prevailing mode of payment for both online aswell as regular purchase, fraud relate with it are also accelerating. Fraud detection is concerned with not only capturing thefraudulent events, but also capturing of such activities as quickly as possible. The use of credit cards is common in modern daysociety. Fraud is a millions dollar business and it is rising every year This will also signify how a comprehensive fraud detectionsystem could help maintain the cost of detecting fraud, and Losses due to fraud, i.e., the total cost of fraud, under manageablelevels. The main focushere will be mostly on Visa and MasterCard type transactions.